Peripheral CB1 Receptor Neutral Antagonist, AM6545, Ameliorates Hypometabolic Obesity and Improves Adipokine Secretion in Monosodium Glutamate Induced Obese Mice - Ma, Haiming; Zhang, Guina; Mou, Chunrong; Fu, Xiujuan; Chen, Yadan (Frontiers in Pharmacology, 2018)
Effect of peripheral cannabinoid receptor 1 (CB1R) blockade by AM6545 in the monosodium glutamate (MSG)-induced hypometabolic and hypothalamic obesity was observed, and the impact on intraperitoneal adipose tissue and adipokines was investigated. The MSG mice is characterized by excessive abdominal obesity, and combined with dyslipidemia and insulin resistance. 3-week AM6545 treatment dose-dependently decreased the body weight, intraperitoneal fat mass, and rectified the accompanied dyslipidemia include elevated serum triglyceride, total cholesterol, free fatty acids, and lowered LDLc level. Glucose intolerance and hyperinslulinemia were also alleviated. But AM6545 didn’t impact the food-intake consistently through the experiment. In line with the reduction on fat mass, the size of adipocyte was reduced markedly. Most interestingly, AM6545 showed significant improvement on levels of circulating adipokines including lowering leptin, asprosin and TNFα, and increasing HMW adiponectin. Correspondingly, dysregulated gene expression of lipogenesis, lipolysis, and adipokines in the adipose tissue were nearly recovered to normal level after AM6545 treatment. Additionally, western blot analysis revealed that AM6545 corrected the elevated CB1R and PPARγ protein expression, while increased the key energy uncoupling protein UCP1 expression in adipose tissue. Taken together, the current study indicates that AM6545 induced a comprehensive metabolic improvement in the MSG mice including counteracting the hypometabolic and hypothalamic obesity, and improving the accompanied dyslipidemia and insulin resistance. One key underlying mechanism is related to ameliorate on the metabolic deregulation of adipose tissue, the synthesis and secretion of adipokines were thus rectified, and finally the catabolism was increased and the anabolism was reduced in intraperitoneal adipose tissue. Findings from this study will provide the valuable information about peripheral CB1R antagonist in managing hypometabolic obesity.